(untitled) (Scientific journal of the Fergana State University, 2023)
This article will discuss the features of artistic reflection on mourning ceremonies in the poems of the People’s poet of Tajikistan, Farzonai Khujandi. The main purpose of the research was to study the poet’s new interpretation of the words, terms, and phrases with poetic art and skill, which express elements of the mourning ceremony.